2023
DOI: 10.1530/ec-22-0416
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COVID-19 infections in patients with adrenal insufficiency and excess

Abstract: Background: Information on clinical outcome of coronavirus disease 19 (COVID-19) infection in patients with adrenal disorders is scarce. Methods: A collaboration between the ESE Rare Disease Committee and ENDO-ERN via the European Registries for Rare Endocrine Conditions (EuRRECa) allowed the collection of data of 64 cases (57 adrenal insufficiency (AI), 7 Cushing’s syndrome) that had been reported by 12 centres in 8 European between January 2020 and December 2021. Results: Of all 64 patients, 23 were males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Respondents who acquired the infection described a mild disease, with few requiring hospitalization or critical care and only 1 death reported. A mild course of COVID-19 infections has been reported among patients with hereditary hemorrhagic telangiectasia in Italy [ 50 ], rare endocrine diseases in a European registry study [ 38 ], lysosomal storage diseases in London [ 79 ], and Gaucher disease in New York [ 42 ]; in a large group of patients with RD in Brazil [ 43 ]; and among people with myasthenia gravis in a subanalysis of this survey [ 52 ]. These reassuring findings are in contrast with higher COVID-19–related mortality among patients with RD in Hong Kong hospitals compared with in-patients from the general population [ 37 ] and people with neurological and neurodevelopmental diseases in a Genomics England cohort study [ 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…Respondents who acquired the infection described a mild disease, with few requiring hospitalization or critical care and only 1 death reported. A mild course of COVID-19 infections has been reported among patients with hereditary hemorrhagic telangiectasia in Italy [ 50 ], rare endocrine diseases in a European registry study [ 38 ], lysosomal storage diseases in London [ 79 ], and Gaucher disease in New York [ 42 ]; in a large group of patients with RD in Brazil [ 43 ]; and among people with myasthenia gravis in a subanalysis of this survey [ 52 ]. These reassuring findings are in contrast with higher COVID-19–related mortality among patients with RD in Hong Kong hospitals compared with in-patients from the general population [ 37 ] and people with neurological and neurodevelopmental diseases in a Genomics England cohort study [ 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…There are very few studies on the outcome of patients with AI and COVID-19 during the pandemic. Eight crosssectional studies have described self-reported outcome in patients with AI during suspected COVID-19 infection [15][16][17][18][19][20][21][22]. One of the studies, which included patients with benign pituitary lesions without AI as controls, reported no difference between patients with AI compared with patients without AI with respect to symptoms or hospitalization at the start of the pandemic [15].…”
Section: Discussionmentioning
confidence: 99%
“…Data on outcome following COVID-19 infections in patients with AI are sparse due to the rarity of the disorder, and evidence is limited by small sample sizes, heterogeneity in terms of study designs and a general lack of matched control groups [15][16][17][18][19][20][21][22]. The aim of this study was therefore to investigate the risk of contracting COVID-19, as well as the risk of hospital admission, intensive care and death due to COVID-19, in a nationwide unselected cohort of patients with AI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a registry platform that minimises reporting burden, the platform can also be adapted to serve the needs of several networks that are interested in understanding the occurrence of multiple rare conditions or events. For instance, during the recent COVID-19 pandemic, the e-REC platform was used to collect essential data concerning specific groups of patients with rare endocrine conditions, who were also affected by COVID-19 ( 15 ). Thus, e-REC can be used for continued surveillance of conditions or for a fixed period.…”
Section: Discussionmentioning
confidence: 99%